Distinct effects of acute exercise and breaks in sitting on working memory and executive function in older adults: a three-arm, randomised cross-over trial to evaluate the effects of exercise with and without breaks in sitting on cognition. Issue 13 (29th April 2019) - Wheeler, Michael J; Green, Daniel J; Ellis, Kathryn A; Cerin, Ester; Heinonen, Ilkka; Naylor, Louise H; Larsen, Robyn; Wennberg, Patrik; Boraxbekk, Carl-Johan; Lewis, Jaye; Eikelis, Nina; Lautenschlager, Nicola T; et al.
Abstract : Background: Sedentary behaviour is associated with impaired cognition, whereas exercise can acutely improve cognition. Objective: We compared the effects of a morning bout of moderate-intensity exercise, with and without subsequent light-intensity walking breaks from sitting, on cognition in older adults. Methods: Sedentary overweight/obese older adults with normal cognitive function (n=67, 67±7 years, 31.2±4.1 kg/m 2 ) completed three conditions (6-day washout): SIT (sitting): uninterrupted sitting (8 hours, control); EX+SIT (exercise + sitting): sitting (1 hour), moderate-intensity walking (30 min), uninterrupted sitting (6.5 hours); and EX+BR (exercise + breaks): sitting (1 hour), moderate-intensity walking (30 min), sitting interrupted every 30 min with 3 min of light-intensity walking (6.5 hours). Cognitive testing (Cogstate) was completed at four time points assessing psychomotor function, attention, executive function, visual learning and working memory. Serum brain-derived neurotrophic growth factor (BDNF) was assessed at six time points. The 8-hour net area under the curve (AUC) was calculated for each outcome. Results: Working memory net AUC z-score·hour (95% CI) was improved in EX+BR with a z-score of +28 (−26 to +81), relative to SIT, −25 (−79 to +29, p=0.04 vs EX+BR). Executive function net AUC was improved in EX+SIT, −8 (− 71 to +55), relative to SIT, −80 (−142 to −17, p=0.03 vs EX+SIT). Serum BDNF net AUC ng/mL·hour (95% CI) was increased in both EX+SIT, +171 (−449 to +791, p=0.03 vs SIT), and EX+BR, +139 (−481 to +759, p=0.045 vs SIT), relative to SIT, −227 (−851 to +396). Conclusion: A morning bout of moderate-intensity exercise improves serum BDNF and working memory or executive function in older adults, depending on whether or not subsequent sitting is also interrupted with intermittent light-intensity walking. Trial registration number: ACTRN12614000737639.